Study on the electromagnetic properties of the [sc][q¯b¯] and [sc][s¯b¯] states with JP=1 - Özdem, Ulaş (European physical journal plus, 2025)
A systematic study of the electromagnetic properties of exotic states is conducted to elucidate their nature, which continues to be the subject of controversy and incomplete understanding in the field. In this study, the magnetic dipole and quadrupole moments of the tetraquarks [ s c ] [ q ¯ b ¯ ] and [ s c ] [ s ¯ b ¯ ] with J P = 1 + are extracted in the context of a compact diquark-antidiquark configuration with the help of the QCD light-cone rules method. The magnetic dipole moments are given as μ [ s c ] [ u ¯ b ¯ ] = - 2 . 12 - 0.59 + 0.74 μ N , μ [ s c ] [ d ¯ b ¯ ] = 1 . 66 - 0.46 + 0.60 μ N , and μ [ s c ] [ s ¯ b ¯ ] = 2 . 01 - 0.50 + 0.61 μ N . The order of magnitude of the magnetic dipole moments would suggest that these outcomes may be achievable in forthcoming experiments. The magnetic and quadrupole moments of hadrons represent another important observable, along with their mass and decay width, contributing to our understanding of the underlying quark structure and dynamics. Therefore, we hope that the results of this study will prove useful in theoretical and experimental investigations, which we anticipate will be an interesting research topic.